Experimental Investigation of Unsteady Static Pressure Field Behind a Circular Cylinder - Suchý Jakub; Nožička Jiří; Papež Václav (EPJ Web of Conferences, 2022)
In this paper a measurement of a static pressure in the wake behind a circular cylinder for the different Reynolds numbers is presented. For this purpose, a static pressure probe with built-in pressure transducer was used. The main goal is to describe the unsteady pressure field behind the cylinder and determine a frequency of the generated Von Kármán vortex street. The measurement was conducted in a low speed wind tunnel for a cylinder with 110 mm in diameter. The results were compared to an unsteady RANS simulation.